Nucleophilicity at copper(-I) in a compound with a Cu–Mg bond - Ross A. Jackson; Nicholas J. Evans; Dawid J. Babula; Thomas M. Horsley Downie; Rex S. C. Charman; Samuel E. Neale; Mary F. Mahon; David J. Liptrot (Nature Communications)
Abstract Copper is ubiquitous as a structural material, and as a reagent in (bio)chemical transformations. A vast number of chemical reactions rely on the near-inevitable preference of copper for positive oxidation states to make useful compounds. Here we show this electronic paradigm can be subverted in a stable compound with a copper-magnesium bond, which conforms to the formal oxidation state of Cu(-I). The Cu-Mg bond is synthesized by the reaction of an N-heterocyclic carbene (NHC) ligated copper alkoxide with a dimeric magnesium(I) compound. Its identity is confirmed by single-crystal X-ray structural analysis and NMR spectroscopy, and computational investigations provide data consistent with a high charge density at copper. The Cu-Mg bond acts as a source of the cupride anion, transferring the NHC-copper fragment to electrophilic s-, p-, and d-block atoms to make known and new copper-containing compounds.